ANALISIS EFEKTIVITAS VIDEO HSE INDUCTION BERBASIS MOTION GRAPHIC PADA PEKERJA DI PT. WASCO ENGINEERING INDONESIA - Sonia Tasha Camilla; Fadli Suandi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
This study discusses making video motion graphics for HSE induction at PT Wasco Engineering Indonesia. Usually, HSE induction delivery is carried out through presentation of material by trainers through presentation slides. However, an idea arose to create a new media that is more effective and keeps up with technological developments in the multimedia field, namely video motion graphics. This research is in the manufacturing process using the Villamil-Molina development method which has several stages including development, preproduction, production, post production and delivery. To analyze the effectiveness of video motion graphics, the EPIC model is used with four dimensions, namely empathy, persuasion, impact, and communication. The results of the analysis using the EPIC model show a value of 4.03, which indicates that video motion graphics are considered effective for HSE induction activities at PT Wasco Engineering Indonesia.